X-ray diffraction and photoelectron spectroscopy analyses of MXene electrode material used in energy storage applications - a review - Mohd Abid, Mohd Asyadi 'Azam; Kosnan, Muhammad Akmal; Munawar, Rose Farahiyan; Tee, Chee Yin; Mohd Halim, Nurhaliana Shazwani; Klimkowicz, Alicja; Takasaki, Akito (Walter de Gruyter GmbH, 2024)
X-rays have many uses in screening and materials characterization applications. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) analysis are among them. From the XRD data, a crystal structure can be determined by analysis of the XRD pattern, intensity, and positions of the peaks. Information about the crystallographic space group, lattice parameters, preferred orientation, and crystallite size can be derived. XPS examines the surface chemical state of a sample. This review will focus exclusively on MXene compounds and their analysis using XRD and XPS. MXene are layered compounds with a strong potential for application in energy storage. Since MXenes are two-dimensional (2D) transition metal carbides and nitride, the material exhibit signals indicating the presence of specific transition elements, 1s carbon, and 1s oxygen. Additionally, there is a possibility of detecting an element from group 13 or 14 of the periodic table, such as aluminum, nitrogen, or fluorine. A comprehensive study based on XRD and XPS analytical techniques of 2-dimensional electrode materials may provide advancement in the field of energy storage. MXene especially deserve attention due to their remarkable structural and electrochemical characteristics, such as conductivity, topological, and surface area, which attracted numerous researchers worldwide.